A Cultural Dimension of American-Indonesian “Fast Food Diplomacy” - Sri Herminingrum (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2020)
This article endeavors to elucidate the establishment of international relations between America and Indonesia by means of fast food franchises from a cultural dimension point of view. Since diplomacy in this context embraces the coexistent expression of cultures, the object highlighted in the research is the presence of American fast food icons, which are represented by Kentucky Fried Chicken (KFC) and McDonald’s. The concepts of cultural change are used as the basis of data analysis from this one-year field observation over the two franchises in Malang, East Java, Indonesia. This analysis aims (1) to uncover the innovations of KFC and McDonald’s outlets to devise new forms of their fast food that fit Indonesian food habits, as well as to trace (2) the spread of their global ideas in the everyday habits of Indonesians, and (3) the influence of the existence of both upon the burgeoning AmericanIndonesian hybridized food culture. The result discloses that the business activity of KFC and McDonald’s has not only created an affinity for economic benefit towards America and Indonesia through the hands of private enterprise, but has also engendered the diversified ‘fast-food genre’.